Agricultural Education Program on Biosaka Production to Reduce Dependence on Chemical Fertilizers and Pesticides in Sidosari Village - Rakhmat Pebriyanto; Widya Mas Mardavam Jayanti; Samsudin Al Hidayat; Fahrian Respatiaji; Muhammad Ramadhana Hasan Mansur; Lily Miftahul Jannah; Angela Mery Prastikasari; Hermawati Imelia Putri; Mirza Suci Mubarokah; Rahmatia Salsabil; Johan Pamungkas (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Sidosari Village in Salaman District, Magelang Regency, has strong agricultural potential, mainly from rice farming as the main source of income. However, heavy use of chemical fertilizers and pesticides has caused soil degradation, ecological imbalance, and health problems for farmers. This community service program introduced Biosaka, a natural elicitor made from local weeds, as an environmentally friendly alternative. Biosaka strengthens plant resistance to pests and diseases and can reduce chemical fertilizer use by 50 to 90 percent. The program used Participatory Action Research (PAR) with stages of problem identification, socialization, hands-on training, observation, and reflection. It was held from July 15 to August 2, 2024, at Sidosari Village Hall and involved representatives from 30 farmer groups. Participants successfully produced Biosaka solutions that met quality criteria, including homogeneity, absence of sediment, and appropriate pH and TDS levels. They also demonstrated high enthusiasm and provided positive feedback on the accessibility and benefits of Biosaka. The activity fostered collaboration among students, farmers, and the community, thereby increasing awareness and skills in sustainable agricultural practices. Results indicate potential improvements in soil health, reduced production costs, and long-term environmental sustainability in local agriculture.